Mindful Eating: Connecting With the Wise Self, the Spiritual Self - Kristeller, Jean L.; Jordan, Kevin D. (Frontiers in Psychology, 2018)
In the Mindfulness-Based Eating Awareness Training program (MB-EAT), which lasts 12 sessions, mindfulness practice is taught, mindful eating is cultivated, and self-awareness and self-acceptance are enhanced. An integrative concept is the value in cultivating ‘wisdom’ in regard to creating a new and flexible relationship to eating and food, rather than following externally determined rules and guidelines. Several clinical trials involving several versions of MB-EAT have documented substantive improvement in how people relate to their eating and food, including individuals with both binge eating disorder and subclinical eating issues. Based on the traditional value of contemplative practices for cultivating spiritual engagement, and on evidence from research showing that spiritual well-being increases in the MBSR program, we hypothesized that the MB-EAT program would also engage this aspect of experience, as assessed by the FACIT-Sp, and that increases in spiritual well-being would relate to other measures of adjustment such as emotional balance and improvement in disordered eating. A sample of participants (N=117) with moderate to morbid obesity, including 25.6% with binge eating disorder, were randomly assigned to MB-EAT or to a wait-list control, and assessed on the FACIT-Sp, along with other measures at baseline, immediate post, and 2-month followup. There were significant group x time interactions for the FACIT-Sp factors of Meaning & Peace, and Faith. Change in these factors correlated with change on both emotional adjustment, eating regulation, and aspects of mindfulness as measured by the FFMQ. Results are discussed in terms of the role that mindfulness plays in cultivating ‘wise mind’ and the related value of spirituality. It is argued that the core elements of the MB-EAT program lead to meaningful spiritual engagement, which plays a role in people’s ability to improve and maintain overall self-regulation.